History of Sexual Violence Victimization and Weapon Carrying Among Adolescents: Findings from the 2019 Youth Risk Behavior Survey - Baiden, Philip (American journal of criminal justice, 2022)
Although prior studies have examined the association between sexual violence victimization and violent behaviors, few studies have investigated the association between sexual violence victimization and weapon carrying among adolescents in the United States. The objective of this study was to investigate the association between sexual violence victimization and weapon carrying among adolescents. Data for this study came from the 2019 Youth Risk Behavior Survey. An analytic sample of 13,605 adolescents aged 12-18 years old was analyzed using binary logistic regression. The outcome variable investigated in this study was weapon carrying during the past 30 days, and the main explanatory variable investigated was sexual violence victimization during the past year. Of the 13,605 adolescents, 13.6% reported carrying a weapon at least once during the past 30 days. A little over one in ten adolescents (11.8%) experienced sexual violence victimization during the past year. In the multivariable logistic regression, adolescents who were victims of sexual violence had 1.82 times higher odds of reporting carrying a weapon when compared to their non-victimized counterparts (AOR = 1.82, p < .001, 95% CI = 1.44-2.30). Symptoms of depression partially attenuate the association between sexual violence victimization and weapon carrying. Other significant factors associated with weapon carrying include male gender, bullying victimization, obesity, and substance use. Adolescents who self-identified as Black/African American, Hispanic, or Asian were significantly less likely to carry a weapon. The findings of this study underscore the importance of improving safety in schools by developing appropriate interventions to reduce sexual violence and weapon carrying among adolescents.